Letter to Jane Tolmach from S. Floyd Mori - S. Floyd Mori:::::: (1976)
In a May 19, 1976 letter, Assemblyman S. Floyd Mori thanked Jane Tolmach for attending a reception for him in Montebello. He and his wife, Irene, appreciated the opportunity to meet her and others from the Los Angeles area. Mori expressed his hope that she would succeed in her upcoming election. He also offered his assistance to her campaign. The letter concluded with thanks for her support.